Gambaran Perilaku Merokok Pada Siswi SMA Negeri 3 Sukoharjo - Fatahillah, Muhammad, Siti Arifah, S.Kp., M.Kes (2016)
Adolescence is a period of growth and development that is experiencing a transition from children to adulthood is accompanied by a change and development in all aspects and functions in entering a period of new and accompanied by changes in a person which has the characteristics corresponding to the function of the new demands in the environment, family or in social , Smoking behavior in adolescents is one of the effects of those changes. In general, smoking behavior conducted by teenage boys, but data in Indonesia showed slightly, the number of smokers in young women has increased, so did occur in adolescent girls State Senior High School 3 of Sukoharjo. This research aims to find a description of schoolgirls smoking behaviour in State Senior High School 3 of Sukoharjo . This research is descriptive. Sample study was 14 schoolgirls smokers in state Senior High School 3 of Sukoharjo with accidental sampling technique. Collecting data using questionnaires were analyzed using descriptive analysis test (univariate). Conclusion of the study are (1) the reason schoolgirls State Senior High School 3 of Sukoharjo had smoking behavior, mostly by smoking they feel slang, (2) Duration schoolgirls State Senior High School 3 of Sukoharjo do most of the smoking behavior is 1-3 months, (3) A place that usually to smoke by schoolgirls State Senior High School 3 of Sukoharjo mostly on the roads, (4) The number of cigarettes that is spent at that time by schoolgirls State Senior High School 3 of Sukoharjo mostly one piece, (5) Sources of cigarettes obtained schoolgirls State Senior High School 3 of Sukoharjo mostly requested from friends, (6) Background of the family members in schoolgirls State Senior High School 3 of Sukoharjo who smoke most have a family member with a background of smokers.